ULTRA PETITA DALAM PUTUSAN PERADILAN TATA USAHA NEGARA SEBAGAI UPAYA PERLINDUNGAN HUKUM BAGI MASYARAKAT PENCARI KEADILAN ( TINJAUAN HUKUM PROGRESIF) - , Delta Arga Prayudha, Joko Setiono, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis is start from opinion that in doing justice power responsibility, The Judge of PTUN all this time is frequently made incompetent penaltys, thought some lawyers. The example of this incompetent penalty is penalty made with ultra petition. It is important to see whether ultra petition is banned by Undang-Undang Peradilan Tata Usaha Negara, and whether that ultra petition doctrin is applicable for all of judge in all of court. In this case is need to be known, what the consideration for that ultra petition penalty is, so it can be known in what case The Judge of PTUN allowed to give ultra petition penalty. From these considerations, we can conclude if progresif law enforcement is really exist. This legal research using normative juridical approach method with analitical description research spesification. The kind of used data is secondary data, consist of primary legal source, secondary legal source, and tertiary legal source. The data collecting techniques used is library research and from collected datas analyzed with normative-qualitative. From the research, it can be concluded that doctrin of ultra petition forbidding for The Judge is not absolutely and common valid. The way The Judge of PTUN did in making ultra petition penalty in principle is the form of progressif law establishment, but whatever the creativity did by the lawyer, nonsense if it is not for actualize substantive justice.